A Retrospective Analysis of Salivary Gland Tumor Cases: Histological Variations and Clinical Outcomes - Kunzes Dolma; Anu Sumi Issac; Renuka Gupta; Surya Kumari Achanta; Pallavi P. Channe; Oruganti Venkata Ramanand; Anil Managutti (Wolters Kluwer Medknow Publications, 2024)
Background: Salivary gland tumors (SGTs) present a diagnostic challenge due to their diverse histological subtypes and variable clinical behavior. Methods: This research conducted a retrospective analysis of SGT cases diagnosed and managed at a tertiary care center between 2017 and 2022. Clinical and pathological data were retrieved from medical records and histopathology reports. Statistical analysis was performed to identify factors associated with recurrence and survival outcomes. Results: A total of 150 SGT cases were included, comprising 70% benign and 30% malignant tumors. Pleomorphic adenoma and adenoid cystic carcinoma were the most prevalent benign and malignant subtypes, respectively. Surgical resection was the primary treatment modality, with varying recurrence rates observed among different treatment groups. Conclusion: The current study provides insights into the histological variations and clinical outcomes of SGTs. Surgical resection remains the mainstay of treatment, with adjuvant therapy reserved for cases with adverse prognostic factors. Further research is needed to optimize therapeutic strategies and improve patient outcomes.